178k views
7 votes
Help on this question pleaseeeeeeee

Help on this question pleaseeeeeeee-example-1

2 Answers

7 votes

Answer:

answer is 46

Explanation:

Solution for f-27=19 equation:

Simplifying

f + -27 = 19

Reorder the terms:

-27 + f = 19

Solving

-27 + f = 19

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '27' to each side of the equation.

-27 + 27 + f = 19 + 27

Combine like terms: -27 + 27 = 0

0 + f = 19 + 27

f = 19 + 27

Combine like terms: 19 + 27 = 46

f = 46

Simplifying

f = 46

User Randy Larson
by
4.7k points
3 votes

Explanation:

F-27=19

F= 19+27

F=46

I hope it is helpful have a nice day

User Hudson Worden
by
4.9k points